(untitled) (Global Journal of Management and Business Research, 2020)
The purpose of this paper was to examine the relationship between organizational trustworthiness and employee innovative work behaviour. The paper is designed as a theoretical paper and as such discusses related theories which conceptualize and detail the relationship between the variables. The content of the paper addressed the nature and implications of organizational trustworthiness for employee innovative work behaviour by offering insight on issues which bother on employee work expectations, as well as the relationship between managers/supervisors and their employees. In conclusion, it was stated that there is the need for organizations to emphasis on practices and qualities which express their substantial levels of benevolence, integrity and competence as a way of enhancing their trustworthiness and as such, increasing employee innovative behaviour within the workplace.